Plurality versus Diversity: A note on the views of Plato, Aristotle and Augustine of Hippo with regard to language and thought - Aparició, Maria Albisu (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
In the present study is raised the question of the dialectic between linguistic plurality and human diversity , such as it seems to be configured in the works of Plato, Aristotle and Augustine in function of the different positions that these authors embrace about the relations between language and thought